1996
DOI: 10.1097/00004647-199607000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Changes in Local Cerebral Glucose Utilization in the Rat

Abstract: Summary: In exercise, little is known about local cere bral glucose utilization (LCGU), which is an index of functional neurogenic activity. We measured LCGU in resting and running (=85% of maximum O2 uptake) rats (n = 7 in both groups) previously equipped with a tail artery catheter. LCGU was measured quantitatively from 2-deoxY-D-[1-14C]glucose autoradiographs. During exer cise, total cerebral glucose utilization (TCGU) increased by 38% (p < 0.005). LCGU increased (p < 0.05) in areas involved in motor functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
10

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(70 citation statements)
references
References 19 publications
2
58
0
10
Order By: Relevance
“…Depending on the type of sport, exercise should result in activity of structures involved in perceptual function and memory, particularly TOP and the sensory thalamus. Local cerebral glucose metabolism and utilization measured in running rats has confirmed this pattern of activity (Vissing, Anderson, & Diemer, 1996). Since such a large part of the brain is devoted to perception and motor output, there is a widespread activation of numerous structures across the entire brain during exercise.…”
Section: Endurance Runningmentioning
confidence: 56%
“…Depending on the type of sport, exercise should result in activity of structures involved in perceptual function and memory, particularly TOP and the sensory thalamus. Local cerebral glucose metabolism and utilization measured in running rats has confirmed this pattern of activity (Vissing, Anderson, & Diemer, 1996). Since such a large part of the brain is devoted to perception and motor output, there is a widespread activation of numerous structures across the entire brain during exercise.…”
Section: Endurance Runningmentioning
confidence: 56%
“…1a). Although exercise might potentially affect CBV by increasing metabolism and cerebral blood flow, previous studies (31,32) have shown that exercise-induced changes in metabolism should manifest during, not after, the exercise regimen. Thus, the observed spatiotemporal profile with which CBV emerged fits better with a model of exercise-induced angiogenesis in the dentate gyrus.…”
Section: Resultsmentioning
confidence: 98%
“…Although no substantial LCMRglu changes were observed after physical training, exercise did reverse the low metabolic rates in several structures of animals with epilepsy. Vissing et al (1996) reported higher local cerebral glucose utilization in the auditory and visual cortex during exercise, suggesting that these changes are not related directly to the exercise per se, but to higher mental alertness in exercise than in resting rats. Since physical activity does need a certain level of alertness, the increased attention and vigilance observed during physical activity could reduce the number of seizures (Kuijer 1980).…”
Section: Epilepsy and Exercise: Animals Studiesmentioning
confidence: 95%